The Impact of Modern Teaching Strategy in Enhancing the Learning Skills of the Grade 9 Students at Holy Rosary College Foundation - Divina, Daniela B.; Miparanum, May Grace D.; Pondavilla, John Francis; Zita, Cris T. (Institut Agama Islam Negeri Lhokseumawe, 2023)
Modern teaching strategies can help students create activities that allow them to cooperate and learn from one another while having fun. Research has shown that collaborative learning fosters students’ academic learning style in addition to help them acquire Higher Order Thinking Skills (HOTS). Thus, this study aims to determine the most effective way for students to acquire modern teaching strategies. A total of 30 students (Grade 9) from Junior High School of Holy Rosary College Foundation participated in this study, with data collected through the use of a survey questionnaire. The main aim of the study is to find out how modern teaching strategy affects students’ ability to learn. Drawing upon modern teaching strategy, this research suggests that implementing innovative teaching methods (i.e. collaborative learning, gamification and thinking-based learning) can contribute to boost high school students’ confidence. Moreover, these strategies also foster the development of students’ social skills and promote communicative interaction with their peers. Equally important, modern teaching strategy yields benefits for both students and teachers.